Corrosion Fatigue Studies on a Bulk Glassy Zr-Based Alloy under Three-Point Bending - Grell, Daniel; Wilkin, Yannic; Gostin, Petre F.; Gebert, Annett; Kerscher, Eberhard (Frontiers in Materials, 2017)
Corrosion fatigue (CF) tests were carried out on bulk glassy Zr52.5Cu17.9Al10Ni14.6Ti5 (Vitreloy 105) samples under load-controlled three-point bending conditions with a load ratio of R = 0.1 in 0.01 M Na2SO4 + 0.01 M NaCl electrolyte. During cyclic testing, the bar-shaped specimens were polarized in situ at constant potentials and the current was monitored. Three different anodic potentials within the interval between the pitting potential EP and the repassivation potential ER, and three different load amplitudes were applied. In some cases, in situ microscopic observations revealed the formation of black corrosion products in the vicinity of the crack tip during anodic polarization. Fractographic analysis revealed a clear distinction between two modes of crack growth characterized by smooth dissolution induced regions on the one hand and slim fast fracture areas on the other hand. Both alternating features contributed to a broad striated corrosion fatigue fracture surface. Moreover, further fatigue tests were carried out under free corrosion conditions yielding additional information on crack initiation and crack propagation period by means of the open circuit potential (OCP) changes. Thereby, a slight increase in OCP was detected after rupture of the passive layer due to bare metal exposed to the electrolyte. The electrochemical response increased continuously according to stable crack propagation until fracture occurred. Finally, the fracture surfaces of the corrosion fatigue samples were investigated by energy dispersive X-ray with the objective of analyzing the elemental distribution after anodic dissolution. Interestingly, anodic polarization at a near repassivation potential of -50 mV vs. SCE (Saturated Calomel Electrode, E = 0.241 V vs. SHE, Standard Hydrogen Electrode) led to favorable effects on the fatigue lifetime. In conclusion, all results are conflated to a corrosion fatigue model for bulk glassy Vitreloy 105 under anodic polarization in chloride-containing electrolyte and compared to the previously proposed stress corrosion mechanisms under similar conditions.